Characterization of G-wire formation with guanine-rich sequences - Rosal, Katelyn Grace Agdeppa (Nanyang Technological University, 2021)
Tetrahymena telomeric sequences were discovered to self-assemble into rod-like superstructures called "G-wires" and have great conductive capabilities, as well as the ability to withstand harsh environments, therefore sparking interests in many to incorporate G-wires into many purposes like a drug delivery system and conductive nanowires. Given the many potential impacts of G-wires, it is important that there be reliable characterization of the formation of G-wires, to be reproducibly and consistently produced with intended and accurate dimensions. Factors contributing to the stabilization and formation of g-quadruplexes have been studied thoroughly but the factors for G-wires are still unclear. Different papers have suggested different factors with certain parameters and produced different types of G-wires. Although G-wires may be derived from G-quadruplexes, what causes and stabilizes the formation of G-wires are still ambiguous. To study this, the factors in the formation of G-wires and their resulting effects on the wires need to be known in order to build a system in which G-wires with intended dimensions can be created for their respective uses. This study explores certain factors such as concentrations of substances annealed with the DNA sequences and various cations for the stabilization of G-wire structures while finding other potential factors. It also studies if other guanine-rich sequences may also form higher order structures. Through gel electrophoresis and atomic force spectroscopy, the results are analysed and compared with results of other parameters to conclude the specific effect the respective factor is responsible for, and which factors are most suitable for long G-wire formation.